Pembelajaran Etude Fifty Little Flute Studies OP25 Pada Mahasiswa Instrumen Flute Prodi Pendidikan Musik FBS UNP - Rini Arifa Hidayamastifa; Jagar Lumbantoruan (FBS Universitas Negeri Padang, 2020)
The purpose of this study is to find out how the learning process of Etude Fifty Little Flute Studies is conducted in the flute instrument Major I course in the Music Education Study Program at FBS UniversitasNegeri Padang. This research is a descriptive analysis research by utilizing qualitative data. The implementation of Etude Fifty Little Flute Studies learning in flute instrument major I involved students of 2019 class who just took major I course which was played in 3 repertoires.The study examined the learning process of Etude Fifty Little Flute Studies Op 25 and Op 26 by looking for processes, learning experiences, and learning evaluations.Based on the results of learning conducted, Etude Fifty Little Flute Studies is very influential in the learning process.It is due to the fact that flute instrument major I studentsare still categorized as beginners and are new to the flute instruments and theoretical abilities such as using suspension, legato and staccato techniques.This is proven by students who carry out the process well and practice through the material given. Thus, these students get grades according to their processes.The relation between what is explained by the lecturer and the students theoretically and practically can be done well even though it is not that optimal because there is no direct control through face to face meeting.